An appraisal of the provision of "benefits" as an unfair labour practice in South African labour law - Newaj, Kamalesh (University of Pretoria, 2019)
This thesis seeks to resolve the ambiguities surrounding the use of the unfair labour practice relating to the provision of “benefits” as a dispute resolution mechanism in South African labour law. This mechanism has been plagued with uncertainty, primar-ily because of the lack of a statutory definition of benefits. Evidently, the interpretation and application of benefits have been left to the courts, resulting in two diverse ap-proaches being endorsed. The first one sought to confer a narrow connotation on ben-efits, the rationale being to separate benefits from the definition of “remuneration”. It further sought to limit the use of this unfair labour practice to instances where the benefit claimed was exclusively provided for ex contractu or ex lege. The primary ob-jective was to protect the divide between disputes of right and disputes of interest, a distinction that is recognised and encouraged in our law. The second approach was one that fostered an expansive interpretation of the term, deeming it to be part of re-muneration. Needless to say it resulted in countless items being subject to determina-tion as benefit disputes. Furthermore, it extended benefits beyond those rooted in con-tract or legislation, including those granted or offered subject to the exercise of mana-gerial discretion. The supplementary challenges firstly relate to the absence of statutory direction on the standards of fairness to be applied in evaluating employer conduct. Secondly, the judiciary has provided opportunities for employees to utilise recourse other than the unfair labour practice provisions to address benefit disputes. Such leeway comes in the form of contractual recourse as well as the ability to institute strike action. In search of solutions to the problems identified above, the study explores and anal-yses the history of the unfair labour practice concept. Thereafter, an extensive exam-ination of the developments in this area of the law is undertaken. This includes a com-prehensive analysis of legislation, case law and academic writings. Having docu-mented and analysed the South African position both pre- and post-democracy, the study critically evaluates these sources of law. The study further involves a diagnostic assessment of international legal instruments and foreign law in order to extract best practices. The conclusions reached are, firstly, that an expansive interpretation of benefits is warranted. This is in line with a purposive interpretation of the LRA, which promotes the constitutional right to fair labour practices and international law. This study there-fore proposes a wide-ranging definition of the term benefits. Secondly, standards of substantive and procedural fairness have been found to be applicable in evaluating employer conduct. As such, fairness guidelines based on these standards have been developed. Thirdly, in respect of the alternate avenues available to resolve benefit disputes, it has been found that although there are strong indicators that point to a conclusion that contractual recourse has been supplanted by statutory recourse, such a finding cannot be definitively made. Furthermore, section 64(4) as it stands provides for the right to strike over unilateral changes to terms and conditions of employment, which includes unilateral changes to pre-existing benefits. However, the judiciary can limit the use of this section in benefit disputes by prioritising the substance of the dis-pute over its form. This thesis ultimately proposes the incorporation of a Code of Good Practice into the LRA. The Code of Good Practice: Benefits adopts the principal research findings of this study. It encourages the enforcement of benefit disputes through the dispute res-olution institutions set up by the LRA. The adoption of this Code (The Code of Good Practice: Benefits) will bring certitude to this field of labour law.
URI: https://repository.up.ac.za/handle/2263/72658
Keywords: Labour law; Labour practice; South Africa